Molecular Coevolution of Neuropeptides Gonadotropin-Releasing Hormone and Kisspeptin with their Cognate G Protein-Coupled Receptors - Kim, Dong-Kyu; Cho, Eun Bee; Moon, Mi Jin; Hwang, Jong-Ik; Do-Rego, Jean-Luc; Vaudry, Hubert; Seong, Jae Young (Frontiers in Neuroscience, 2012)
The neuropeptides gonadotropin-releasing hormone (GnRH) and kisspeptin (KiSS), and their receptors gonadotropin-releasing hormone receptor (GnRHR) and kisspeptin receptor (KiSSR) play key roles in vertebrate reproduction. Multiple paralogous isoforms of these genes have been identified in various vertebrate species. Two rounds of genome duplication in early vertebrates likely contributed to the generation of these paralogous genes. Genome synteny and phylogenetic analyses in a variety of vertebrate species have provided insights into the evolutionary origin of and relationship between paralogous genes. The paralogous forms of these neuropeptides and their receptors have coevolved to retain high selectivity of the ligand-receptor interaction. These paralogous forms have become subfunctionalized, neofunctionalized, or dysfunctionalized during evolution. This article reviews the evolutionary mechanism of GnRH/GnRHR and KiSS/KiSSR, and the fate of the duplicated paralogs in vertebrates.